2007
DOI: 10.1093/aje/kwm308
|View full text |Cite
|
Sign up to set email alerts
|

Association of Black Carbon with Cognition among Children in a Prospective Birth Cohort Study

Abstract: While studies show that ultrafine and fine particles can be translocated from the lungs to the central nervous system, the possible neurodegenerative effect of air pollution remains largely unexplored. The authors examined the relation between black carbon, a marker for traffic particles, and cognition among 202 Boston, Massachusetts, children (mean age = 9.7 years (standard deviation, 1.7)) in a prospective birth cohort study (1986-2001). Local black carbon levels were estimated using a validated spatiotempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
221
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(233 citation statements)
references
References 38 publications
7
221
2
3
Order By: Relevance
“…Children, whose mothers were exposed to high concentrations of PM during pregnancy, more often were born with low birth weight and 10 µg/m 3 change in PM 10 accounted for 13.7 g less of weight [59,60,61]. Effect of mothers' exposure to high concentration (above the median 36.3 µg/m 3 ) of fine particles (PM 2,5 ) was reflected in significantly lower mean weight (128.3g) and length (0.9cm) and lower mean head circumference (0.3) of newborns [62]. The researchers in the USA found that mothers who lived in areas with the highest levels of PM 2.5 during their pregnancy delivered slightly smaller babies than their counterparts who lived in areas with lower levels of PM 2.5 exposure.…”
Section: The Adverse Effects Of Air Pollution On Pregnancy Outcomes Amentioning
confidence: 99%
See 1 more Smart Citation
“…Children, whose mothers were exposed to high concentrations of PM during pregnancy, more often were born with low birth weight and 10 µg/m 3 change in PM 10 accounted for 13.7 g less of weight [59,60,61]. Effect of mothers' exposure to high concentration (above the median 36.3 µg/m 3 ) of fine particles (PM 2,5 ) was reflected in significantly lower mean weight (128.3g) and length (0.9cm) and lower mean head circumference (0.3) of newborns [62]. The researchers in the USA found that mothers who lived in areas with the highest levels of PM 2.5 during their pregnancy delivered slightly smaller babies than their counterparts who lived in areas with lower levels of PM 2.5 exposure.…”
Section: The Adverse Effects Of Air Pollution On Pregnancy Outcomes Amentioning
confidence: 99%
“…The effects were roughly equivalent to those seen in children whose mothers smoked ten cigarettes per day while pregnant. The researchers assumed that the harmful effects may be caused by the inflammatory and oxidative effects of the black carbon particles [5]. These findings suggest additional research is needed to investigate the effects of air pollution on the development of intelligence in children and on cognitive decline for people of all ages.…”
mentioning
confidence: 99%
“…Polycyclic aromatic hydrocarbon exposure of pregnant mothers resulted in babies having lower IQs at 5 year than unexposed peers [174]. Black carbon exposure caused downgrading of IQs in babies at 9 year age [175]. Significant reduction in psychomotor, attention and sensory scales, without cognitive impairment was observed in children studying at school located in area of dense city traffick, compared to those from clean air area [176].…”
Section: Studies On Disruptive Exposurementioning
confidence: 97%
“…Light-absorbing carbon (LAC) is getting much more attentions from researchers and policy-makers for its considerable effect on global and regional climate change (Chung and Seinfeld, 2005;Ramanathan and Carmichael, 2008), air quality and human health (Jansen et al, 2005;Suglia et al, 2008), and its reduction has been targeted for near-term global warming mitigation (Shindell et al, 2012). Black carbon (BC) defined optically is a useful qualitative description when referring to light absorbing carbon in atmospheric aerosols .…”
Section: Introductionmentioning
confidence: 99%